2012
DOI: 10.1111/j.1439-0426.2012.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the golden catfish,Horabagrus brachysoma(Günther, 1864), an endemic species of the Western Ghats, India

Abstract: Summary To study the reproductive biology of Horabagrus brachysoma (Günther, 1864), monthly samples were collected from the riverine stretches of Lake Vembanad during 2001–2002. The sexes can be distinguished only during the breeding season; male to female ratio in the exploited catch was 1 : 1.97. The mean LT at first maturity (L50) was 18.5 cm in females and 17.5 cm in males. Absolute fecundity varied between 1100 and 124 000, with a mean of 20 472. The ovary showed group synchronous development and the oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Similarly, linear relationships between fecundity and weight have been reported by other authors (Arthi et al, 2013;Mir et al, 2013;Rao, 1981;Sarkar et al, 2009). In addition to the above, several other studies (Bindu et al, 2012;Buragohain and Goswami, 2014;Gupta et al, 2014) have reported significant relationship between fish length, body weight and ovary weight and fecundity in other catfish viz. Horabagrus brachysoma, Clarias magur and Ompok pabda.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, linear relationships between fecundity and weight have been reported by other authors (Arthi et al, 2013;Mir et al, 2013;Rao, 1981;Sarkar et al, 2009). In addition to the above, several other studies (Bindu et al, 2012;Buragohain and Goswami, 2014;Gupta et al, 2014) have reported significant relationship between fish length, body weight and ovary weight and fecundity in other catfish viz. Horabagrus brachysoma, Clarias magur and Ompok pabda.…”
Section: Discussionmentioning
confidence: 99%
“…Gonads were weighed to the nearest 0.1 g (gonad weight, GW). Gonad development stages were distinguished according to color, relative size, and the presence of vitellogenic oocytes in females or milt in males (West, 1990;Lehodey et al, 1997;Bindu et al, 2012).…”
Section: Fish Sampling and Data Analysesmentioning
confidence: 99%
“…Reproductive strategies in fishes often reflect local adaptation to environmental and ecological conditions (Murua and Saborido-Rey, 2003;Thorsen et al, 2010). Therefore, a thorough understanding of the life history traits is of great significance in conservation biology (Bindu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the pattern of development and ovulation of oocytes, Tyler and Sumpter [36] defined two spawning patterns: single batch and multiple batches. For instance, golden catfish, Horabagrus brachysoma, was typical of single batch species due to its single peak of oocyte diameter distribution [23]. Likewise, A. nigrocauda has a unimodal distribution of oocyte diameter indicating that it is a single batch species.…”
Section: Spawning Seasonmentioning
confidence: 99%
“…For each gonad, its maturity stage was classified as: (1) I, undeveloped; (2) II, early developing; (3) III, later developing; (4) IV, mature; (5) V, spawned; and (6) VI, spent [22]. The gonad development stages were distinguished according to gonad color, relative size and the presence of vitellogenic oocytes in females or milt in males [23][24][25] ( Table 1). Females with vitellogenic oocytes were considered mature.…”
Section: Fish Collectionmentioning
confidence: 99%